2007
DOI: 10.1186/1471-2407-7-214
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucuronosyltransferase UGT1A7 genetic polymorphisms in hepatocellular carcinoma: a differential impact according to seropositivity of HBV or HCV markers?

Abstract: Background:We conducted a case-control study to evaluate the role of UDP-glucuronosyltransferase 1A7 (UGT1A7) polymorphisms in the onset of hepatocellular carcinoma (HCC).Methods:The study included 165 patients with HCC, 134 with cirrhosis and 142 controls without liver disease, matched for age and hospital. All were men younger than 75 years. HCC and cirrhosis patients were stratified according to time since cirrhosis diagnosis.Results:We found a positive association between the UGT1A7*3/*3 genotype and HCC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…UGT1A7 gene. There were six eligible studies including 862 cases and 1546 controls explored the associations between the two SNPs and HCC (Vogel et al 2001;Wang et al 2004;Tseng et al 2005;Borentain et al 2007;Stucker et al 2007;Kong et al 2008). We extracted two polymorphisms' genotype data from the articles to do the meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UGT1A7 gene. There were six eligible studies including 862 cases and 1546 controls explored the associations between the two SNPs and HCC (Vogel et al 2001;Wang et al 2004;Tseng et al 2005;Borentain et al 2007;Stucker et al 2007;Kong et al 2008). We extracted two polymorphisms' genotype data from the articles to do the meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Nine alleles of the UGT1A7 gene, which vary at Gly115Ser, Asn129Lys, Arg131Lys, Glu139Asp, and Trp208Arg (UGT1A7*1-*9), have been discovered to date (Guillemette 2003). Asn129-Lys (rs17868323) and Trp208Arg (rs11692021) decrease the enzyme activity (Vogel et al 2001;Stucker et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a French study of 165 HCC patients genotyped by 5 nuclease allelic discrimination, an association of UGT1A7 * 3 was identified only in patients with HCC related to chronic viral infection (OR 3.4). 179 A similar association was found in a Korean study with 244 HCC patients with chronic hepatitis B infection, who were genotyped by PCR and resequencing to determine UGT1A7 gene variant haplotypes and compared to 223 hepatitis B patients without HCC and 314 normal healthy controls. 180 In this cohort, an OR of 1.45 for HCC development was reported in individuals with UGT1A7 variant haplotypes.…”
Section: Hepatocellular Carcinoma(hcc)mentioning
confidence: 50%
“…Polymorphisms of UGT1A7 could alter the enzymatic activity of the encoded protein [7] and have been reported to be involved in colorectal cancer [20][21][22][23] , lung cancer [24,25] , breast cancer [26] , pancreatic cancer [27] and HCC [9,11,28] . Vogel et al [9] first reported that UGT1A7 * 3 allele could significantly increase HCC risk but Stucker et al [12] found that the association existed only when the case group was restricted to the viral origin. However, Borentain et al [13] failed to find any association between them.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested a link between polymorphism of UGT1A7 and HCC susceptivity [9][10][11] . However, the role of the UGT1A7 still needs further study as other studies gained controversial conclusions [12,13] .…”
Section: Introductionmentioning
confidence: 96%